Posterior urethral polyp in children - Najoua Aballa; Mohamed Oulad Saiad (Wolters Kluwer Medknow Publications, 2021)
Background: Polyps of the urethra is a rare cause of obstruction of the lower urinary tract. The clinical presentation is not specific; the symptoms vary and may be isolated or associated, including acute retention of urine, dysuria, and hematuria. Ultrasound and voiding urethrocystography guide the diagnosis. Urethrocystoscopy confirms the diagnosis and allow the treatment. Our aim is to bring to light this rare condition and report our experience in the management of posterior urethral polyps. Subject and Methods: A retrospective study of posterior urethral polyp presented from 2008 to 2019 was performed. Charts were evaluated for clinical presentation, management, pathology findings, and long term follow-up. Results: Six patients were recorded. Dysuria and hematuria are the most reported features. Ultrasonography and voiding cystourethrogram made the diagnosis in 4 patients out of 6. Urethrocystoscopy made the diagnosis and transurethral resection in all our patients. Conclusions: Posterior urethral polyp is a rare benign tumor in children. Urethrocystscopy allow both diagnostic and therapeutic.